EXPERT SYSTEM FOR DIAGNOSE DIABETES BY USING THE CERTAINTY FACTOR METHOD - Raditya, Muhammad; Fauziah, Fauziah; Winarsih, Endah Tri (Journal of Intelligent Decision Support System (IDSS), 2020)
Diabetes mellitus is a chronic autonim disease caused by interruption of blood sugar regulation, or commonly referred to as diabetes or diabetes. If the disease is not treated with proper care, it can cause dangerous complications, can even threaten the lives of sufferers. Implementation of expert system for diagnosing diabetes mellitus using a web-based certainty factor aims to explore the symptoms displayed in the form of questions - questions that can diagnose different types of diabetes mellitus. Results from this study is a web-based expert system that can detect whether a person's disease or diabetes mellitus. Based on the manual calculation, showed the highest value of 0.